By elimination:
X=-7 and y=2
Answer:
A) 2 + i
Step-by-step explanation:
F(x) = x^3 - 3x^2 + x + 5
0 = x^3 - 3x^2 + x + 5
0 = (x+1)(x^2 - 4x + 5)
Great, now we can separate these two parenthesis expressions because of the Zero Product Property. Start with the simple one:
0 = x + 1
<u>x = -1</u>
We have our first real root! But it doesn't look like that's one of the answer choices, so move on to the other expression:
0 = (x^2 - 4x +5)
This expression can't be factored, so we will use the quadratic formula (which is x =
).
First solve for the positive part:
= (4 + sqrt(16-20)) / 2
= 4 + sqrt(-4) / 2
= 4 + 2i / 2
<u>= 2 + i</u>
Then for the negative part:
= (4 - sqrt(16-20)) / 2
= 4 - sqrt(-4) / 2
= 4 - 2i / 2
<u>= 2 - i</u>
<u></u>
<u>2 + i</u> is answer choice A! Our other roots, <u>2 - i</u> and <u>-1</u>, aren't answer choices.
the reciprocal is 15 by 12
Answer:
(2x+3)(5x+2)
Step-by-step explanation:
10x²+19x+6
multiply to get 60
add to get 19
10x²+19x+6
(10x²+15x)(+4x+6)
factorise:
10x²+15x
5x(2x+3)
4x+6
2(2x+3)
(2x+3)(5x+2)
Answer:
Step-by-step explanation:
Split it into two:
Y<3x
Y<5
X = 1
Y = 3
(1,3)
X = 2
Y = 6
(2, 6)
Plot the line up to y = 4.999999999999999999999 and not higher.